2010
DOI: 10.1074/jbc.m109.016287
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epidermal Growth Factor Receptor Ubiquitination and Trafficking by the USP8·STAM Complex

Abstract: Reversible ubiquitination of activated receptor complexes signals their sorting between recycling and degradation and thereby dictates receptor fate. The deubiquitinating enzyme ubiquitin-specific protease 8 (USP8/UBPy) has been previously implicated in the regulation of the epidermal growth factor receptor (EGFR); however, the molecular mechanisms governing its recruitment and activity in this context remain unclear. Herein, we investigate the role of USP8 in countering ligandinduced ubiquitination and down-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 53 publications
3
106
1
Order By: Relevance
“…FLAG-ubiquitin, Myc-Cbl (BC032851), and MycNrdp1⌬C (BC032637) constructs were generated by PCR and cloned into pcDNA3.1 at BamHI/EcoRI. USP8 and STAM2 constructs used in the bimolecular fluorescence complementation (BiFC) assay (35) have also been previously described (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FLAG-ubiquitin, Myc-Cbl (BC032851), and MycNrdp1⌬C (BC032637) constructs were generated by PCR and cloned into pcDNA3.1 at BamHI/EcoRI. USP8 and STAM2 constructs used in the bimolecular fluorescence complementation (BiFC) assay (35) have also been previously described (18).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that USP8 associates with STAM to mediate direct deubiquitination of activated EGFR, thereby stabilizing the receptor against down-regulation by the lysosome (18). The work presented herein investigates a different role of USP8 in endocytosis through the examination of its effects on trafficking and turnover of the chemokine receptor, CXCR4.…”
mentioning
confidence: 99%
“…The best candidate mammalian Doa4 ortholog is Usp8/UBPY, which can also bind ESCRT-III; however, its role in rescuing Ub from lysosomal degradation has not been specifically determined (Wright et al 2011). Indeed, USP8/ UBPY as well as a similarly positioned DUb, AMSH, can bind both ESCRT-0 and ESCRT-III and a host of experiments looking at different cargoes suggest they can play a role in deubiquitinating cargo before MVB sorting to promote cargo recycling (McCullough et al 2004;Mizuno et al 2005;Bowers et al 2006;Berlin et al 2010;Zhou et al 2013), cargo deubiquitination after sorting as a way to release them from the ESCRT apparatus and promote sorting into MVBs (Alwan and van Leeuwen 2007;Balut et al 2011), or as a way of deubiquitinating ESCRT components to rescue them from degradation or inactive conformations (Row et al 2007;Sierra et al 2010). One of the interesting aspects of cargo deubiquitination in the final stages of sorting is that it predicts that cargo is sorted into a domain capable of trapping Ub cargo such that it cannot escape upon deubiquitination.…”
Section: Ubiquitin-dependent Sorting In Endocytosismentioning
confidence: 99%
“…In addition, it has been reported that Usp8 can interact with the ESCRT-0 component STAM via its SH3 domain and that its depletion results in accelerated degradation of EGF receptor in the lysosome, strongly suggesting that Usp8-dependent deubiquitylation of EGF receptor prevents EGF receptor from being recognized by the ESCRT machinery, a recognition depending on ESCRT-0 component Hrs (Berlin et al, 2010, Rao et al, 2011. Furthermore, the ability of Usp8 to bind both ESCRT-I and ESCRT-III suggests a dual function for Usp8 in receptor sorting.…”
Section: Usp8mentioning
confidence: 99%
“…However, other studies have shown that USP8 can also act , earlier at the level of ESCRT-I, by preventing entry into multivesicular bodies promoting recycling. The interaction of USP8 to both ESCRT-I and ESCRT-III indicates a complex role for this DUB in sorting of endosomal cargo (Berlin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%